1989
DOI: 10.2527/jas1989.6781933x
|View full text |Cite
|
Sign up to set email alerts
|

Index Selection for Components of Litter Size in Swine: Response to Five Generations of Selection

Abstract: Selection for an index of ovulation rate (OR) and embryo (fetal) survival rate (ES) to 50 d of gestation (I = 10.6 x OR + 72.6 x ES) was practiced for five generations in a line that was a composite population of the Large White and Landrace breeds of swine. A control line sampled from the same population was selected randomly and mated. Ovulation rate and number of fetuses (FETS) were measured by laparotomy and ES was calculated as FETS/OR. The select line averaged 43 litters by 18 sires and the control line … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
44
3
1

Year Published

1991
1991
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 20 publications
(28 reference statements)
8
44
3
1
Order By: Relevance
“…The genetic change in litter size obtained with Model 3 was approximately .12% of the mean, .012 pigs&, similar to values reported by Kaplon et al (1991b) and Southwood and Kennedy (1991). When selection was applied only to litter size or t o traits related to litter size, such as ovulation rate and embryonic survival, larger changes in litter size have been reported (Neal et al, 1989;Lamberson et al, 1991).…”
Section: Geneticsupporting
confidence: 68%
“…The genetic change in litter size obtained with Model 3 was approximately .12% of the mean, .012 pigs&, similar to values reported by Kaplon et al (1991b) and Southwood and Kennedy (1991). When selection was applied only to litter size or t o traits related to litter size, such as ovulation rate and embryonic survival, larger changes in litter size have been reported (Neal et al, 1989;Lamberson et al, 1991).…”
Section: Geneticsupporting
confidence: 68%
“…Conversely, the value obtained for weight at puberty is larger than most literature estimates (Young et al, 1978;Hutchens et al, 1981 (Neal et al, 1989) and with estimates obtained in mice and rabbits (Clutter et al, 1990;Blasco et al, 1993b (Young et al, 1977), 50 days of gestation (Neal et al, 1989) or at birth (Young et al, 1978) is observed. This may be due to differences in the populations studied, but may also indicate that uterine competition tends to increase throughout gestation.…”
contrasting
confidence: 44%
“…Also, there may be a negative correlation among some of the component traits, resulting in a low heritability. Some authors observed greater response in litter size after selecting for litter components (Neal & Johnson, 1986;Neal et al, 1989;Bennett & Leymaster, 1990). Haley & Lee (1992) concluded that genetic variation in ovulation rate is largely responsible for the genetic variation in number of live pigs born, with no contribution from genetic variation in prenatal survival.…”
Section: Resultsmentioning
confidence: 99%